Productivity and efficiency measurement of the Danish centralized biogas power sector. (July 2016) - Rácz, Viktor J.; Vestergaard, Niels
Abstract: The widespread use of the renewable energy sources in the future's energy production is necessary, in order to avoid the predicted environmental, economic and social effects which can be derived from the overuse of fossil fuels. Denmark has announced to be fossil fuel independent with a renewable energy based heat and power source by 2050. Theoretically, the centralized biogas combined heat and power plants can play a determinant role in the subsequent Danish energy supply scheme, due to its feature to satisfy base load demand. The productivity and efficiency analysis of the currently operating Danish centralizes biogas CHP power plants is crucial in order to study whether there is a most efficient power plant which can be introduced as a "best practice" innovative technology for the future's Danish biogas power plants. In this paper we use the intertemporal Malmquist total factor productivity DEA method to analyze the change in the efficiency and productivity of the Danish centralized biogas power plants in the period 1992–2005. Highlights: Productivity and efficiency analysis of the Danish centralized biogas power plants. Intertemporal Malmquist total factor productivity DEA method is applied. The average annual TFP increased by 2.5% annually in the examined period. Driver of TFP growth was technical change since "catching up effect" was negative. Aiming technical progress, future energy policy might focus on investment subsidies.